Fuel retention and erosion-deposition on inner wall cladding tiles in JET-ILW. (6th December 2021) - Dittrich, Laura; Petersson, Per; Rubel, Marek; Tran, Tuan Thien; Widdowson, Anna; Jepu, Ionut; Porosnicu, Corneliu; Alves, Eduardo; Catarino, Norberto; Contributors, JET
Abstract: The morphology of beryllium coatings on the Inconel inner wall cladding tiles after JET-ILW campaigns was determined. The focus was on: (i) fuel retention and its share in the overall fuel inventory; (ii) the change of the layer structure and composition. The study is motivated in the view of planned D-T operation in JET. Four tiles were examined: the initial not exposed; one exposed to two campaigns (ILW1-2) and two facing the plasma during ILW1–3. As determined with ion beam and microscopy methods, the initial Be layer (9.0 μ m thick) contained up to 4–5 at.% of impurities, mainly H, O, C, Ni. In the exposed tiles, the impurity content increases to 14–26 at.% (up to 20 at.% O, 1.7 at.% C, 1.0 at.% N, 1.3 at.% Ni and under 0.1 at.% W). The surface composition indicates gettering of O and a long-term retention of N. The Be thickness on the tile exposed to ILW1–2 was between 7.6 and 9.7 μ m, thus indicating erosion in some areas, while the thickness after ILW1–3 increased to 10–12 μ m. The D content was in the range 1.2–3.4×10 17 cm −2 after ILW1–2 and 3.2–10×10 17 cm −2 after ILW1–3 on most of the analyzed area, but in the limiter shadow values up to 58 ×10 17 cm −2 were measured. Taking into account the total area of the Be-coated inner wall cladding tiles, the lower limit of D inventory amounts to 5.3×10 22 atoms corresponding to about 176 mg, i.e. somewhat greater than the amount determined on Be limiters. The formation and spalling-off of Be-O particles was revealed.